2015
DOI: 10.1002/uog.14798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment by three-dimensional power Doppler ultrasound of cerebral blood flow perfusion in fetuses with congenital heart disease

Abstract: Objectives To use three-dimensional (3D) power Doppler ultrasound to investigate cerebral blood flow perfusion in fetuses with congenital heart disease (CHD). Methods The vascularization index (VI), flow index (FI) and vascularization flow index (VFI) in the total MDI (r = 0.243 and 0.203, P = 0.126 and 0.204, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 22 publications
3
38
2
1
Order By: Relevance
“…It was postulated that MCA-PI is associated with cerebral blood flow and brain development in the fetus. In fetuses with HLHS, unlike the findings from Yamamoto et al, 14,15 our study showed that there was no significant difference in MCA-PI, UA-PI, and CPR between HLHS and normal fetuses. [11][12][13] It is also felt that the reduction of MCA-PI normalized by UA-PI may serve as a marker of severity of cardiovascular diseases.…”
Section: Resultscontrasting
confidence: 98%
“…It was postulated that MCA-PI is associated with cerebral blood flow and brain development in the fetus. In fetuses with HLHS, unlike the findings from Yamamoto et al, 14,15 our study showed that there was no significant difference in MCA-PI, UA-PI, and CPR between HLHS and normal fetuses. [11][12][13] It is also felt that the reduction of MCA-PI normalized by UA-PI may serve as a marker of severity of cardiovascular diseases.…”
Section: Resultscontrasting
confidence: 98%
“…Data regarding MCA flow were available in 21 articles (1412 fetuses). Most studies ( n = 14) calculated z ‐scores or percentiles to correct for the effect of the gestational age, using various normal reference populations (Table b) . Seven studies reported absolute values at a specific gestational age .…”
Section: Resultsmentioning
confidence: 99%
“…In eight articles (331fetuses, Table ), postnatal ND outcome was assessed. The correlation with fetal data was studied in seven articles . One study was identified as a possible duplicate .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 It consists of 5 parameters: signs of hydrops, F I G U R E 1 0 T 2 -weighted fetal magnetic resonance image of the chest of a fetus with hypoplastic left heart syndrome and intact atrial septum. 99 The prenatal diagnosis of CHD has shown important benefits to care including earlier age at treatment, decreased perioperative morbidity, and improved neurologic outcome in specific CHD. H = heart; RL = right lung; and LL = left lung.…”
Section: Cardiac Function Assessmentmentioning
confidence: 99%